Triggering near‐infrared luminescence of vanadyl phthalocyanine by charging. (21st April 2022) - Debnath, Sreekanta; Haupa, Karolina A.; Lebedkin, Sergei; Strelnikov, Dmitry; Kappes, Manfred M.
Abstract: Probing electrofluorochromism (EFC) at the molecular level remains challenging. Here we study the strongly charge state‐dependent photoluminescence of vanadyl phthalocyanine. We report vibrationally resolved absorption and laser‐induced fluorescence (LIF) spectra of samples comprising both the mass‐selected neutral molecule (VOPc⋅, a stable radical) and its cation produced upon electron ionization (EI) isolated in 5 K neon matrices. Ionization of the essentially non‐emissive VOPc⋅ forms a high‐spin diradical cation (VOPc +.. ) which shows profound photoluminescence (PL) in the NIR range. This unique phenomenon is potentially of interest for NIR‐emitting electro‐optic devices. Abstract : Charge‐state dependent "on‐off" molecular photo‐switches are of present interest for novel optoelectronics. We have used mass‐selective ion beam deposition into solid Ne at 5 K to compare the spectral properties of vanadyl phthalocyanine (VOPc⋅) with its singly charged cation. Electron detachment from VOPc⋅ leads to a diradical cation (VOPc +.. ) which shows profound NIR photoluminescence. By contrast, VOPc⋅ is essentially non‐emissive.